The Influence of Demographic Factors, Farmer Knowledge, and Motivational Factors on the Adoption of Agricultural Technology Innovation: A Case Study on Dairy Farmers in South Bangka - Fatma Sarie; Wily Mohammad; Nunung Suryana Jamin; Winarto Ramlan (West Science Agro, 2023)
This study looks into the complex factors that affect dairy producers in South Bangka's use of agricultural technology. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used to examine the correlations between farmers' knowledge, motivational factors, technology adoption, and demographic characteristics using a sample of 112 farmers. The results highlight the importance of education and adaptability to change by showing a strong positive correlation between demographic characteristics (age, education) and technological adoption. Farmers' knowledge was found to be a crucial element; a substantial positive association suggests that adoption is positively influenced by a deeper understanding of agricultural technologies. Economic incentives and perceived benefits were found to have significant positive connections with technology adoption, indicating the role that perceived benefits play in encouraging the acceptance of new ideas. The model's significant explanatory and predictive ability was validated by the SEM-PLS study, offering a thorough framework for comprehending and improving South Bangka's adoption of technology. The findings highlight the need of a comprehensive strategy that takes into account farmers' goals, experiences, and degree of knowledge in order to promote the adoption of sustainable technologies.